Synthetic MRI in subarachnoid haemorrhage. Issue 10 (October 2021) - Montejo, C.; Laredo, C.; Llull, L.; Martínez-Heras, E.; López-Rueda, A.; Torné, R.; Garrido, C.; Bargallo, N.; Llufriu, S.; Amaro, S.
Abstract : Aim: To evaluate the reliability of synthetic magnetic resonance imaging (SyMRI) for detecting complications associated with subarachnoid haemorrhage (SAH), such as ischaemic lesions, hydrocephalus, or bleeding complications. Materials and methods: Twenty patients with SAH, who underwent a conventional brain MRI and a SyMRI on a 3 T MRI machine. Comparable conventional and synthetic T2-weighted fluid attenuated inversion recovery (FLAIR) images were acquired. The presence of ischaemic lesions, hydrocephalus, extra-axial blood collections as well as the volumes of grey matter (GMv), white matter (WMv), and cerebrospinal (CSFv) were compared. The acquisition times of both sequences was also analysed. Results: The concordance between the two techniques was excellent for the detection of ischaemic lesions and extra-axial collections (kappa = 0.80 and 0.88 respectively) and good for the detection of hydrocephalus (kappa = 0.69). No significant differences were detected in the number of ischaemic lesions ( p= 0.31) or in the Evans index ( p= 0.11). The WMv and CSFv measures were also similar ( p= 0.18 and p= 0.94, respectively), as well as the volume of ischaemic lesions ( p= 0.79). Compared to conventional MRI, the SyMRI acquisition time was shorter regardless of the number of sections (32% and 6% time reduction for 4 or 3 mm section thickness, respectively). Conclusions: SyMRI allows the detection of potential complications of SAH in a similar way to conventional MRI with a shorter acquisition time. Highlights: SyMRI detects intracranial complications of SAH similarly to conventional MRI. SyMRI acquisitions have quality metrics comparable to conventional MRI. SyMRI acquisition time is shorter compared to conventional MRI.